Clinical Examination Methods in Orthopedics - Manandhar, Rajeev Raj (Kathmandu University Medical Journal, 2010)
Clinical Examination Methods in Orthopedics 2nd Edition, 2010 Author: John Ebnezar Published by Jaypee Brothers Medical Publishers DOI: 10.3126/kumj.v8i2.3578 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 286